Thin film material as well as preparation method and application thereof

By adding a small amount or no first cross-linking agent before the film material is formed and adding the second cross-linking agent later, the problem of equipment clogging caused by pre-cross-linking of the cross-linking agent during the high-temperature forming process of the film material is solved, the production efficiency is improved and the distribution of the cross-linking agent is controllable, thereby improving the overall performance of the film.

CN120682507APending Publication Date: 2025-09-23HANGZHOU FOSTER TECHNOLOGY GROUP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510811000.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing film materials are prone to equipment blockage due to pre-crosslinking reactions of crosslinkers during high-temperature molding, affecting production efficiency. In addition, the traditional crosslinker system is not stable enough under low melt index resins, making it difficult to achieve continuous production.

Method used

After forming a base material with a small amount or no first cross-linking agent, the second cross-linking agent is added by coating, spraying, etc. to control the cross-linking reaction, avoid premature reaction of the cross-linking agent during high-temperature molding, and achieve precise distribution of the cross-linking agent.

Benefits of technology

It effectively avoids equipment blockage, improves production efficiency, extends equipment life, and achieves controllable distribution of cross-linking agents, thereby improving the overall performance and processing performance of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005453954270000181
    Figure BDA0005453954270000181
Patent Text Reader

Abstract

The invention discloses a thin film material and a preparation method and application thereof.The preparation method comprises the steps that (S1) a base film is formed, specifically, a base material is mixed and then added into forming equipment to form the base film, the base material comprises base resin and an optional first cross-linking agent, and when the base material comprises the first cross-linking agent, the first cross-linking agent is added into the base resin in percentage by mass; the mass ratio of the first cross-linking agent to the matrix resin is not higher than 0.1%; and (S2) adding a second cross-linking agent: adding the second cross-linking agent on the base film to form the thin film material. The cross-linking agent is added in a trace amount or not before high-temperature forming and is independently added in the step (S2) after high-temperature forming, cross-linking in the high-temperature forming process can be avoided, and it is avoided that hard particles or coking materials are formed due to local cross-linking to block equipment, so that the production efficiency is improved, meanwhile, the shutdown cleaning frequency is reduced, and the service life of the equipment is prolonged; and the uniformity of the mechanical strength, heat resistance and other properties of the product is improved in the forming process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thin film material preparation, and in particular relates to a thin film material and a preparation method and application thereof. Background Art

[0002] Thin film materials are widely used in industrial production, among which cross-linking agents are key auxiliary agents. By forming a three-dimensional cross-linked network with the resin matrix (such as PVB, ethylene copolymers, etc.), they can significantly improve the mechanical strength, heat resistance and deformation resistance of the material. However, in the process of film processing, the compatibility of the thermal stability of the cross-linker and the processing technology has become a technical bottleneck. Specifically, during high-temperature molding, the decomposition activation energy of the cross-linker (such as peroxide) decreases, and the decomposition rate increases exponentially (following the Arrhenius equation), resulting in a surge in the concentration of free radicals and triggering local pre-cross-linking reactions. This process not only causes a sharp increase in the melt viscosity, but also forms gel particles in areas such as the equipment filter and die flow channel, causing frequent shutdowns for cleaning, which seriously restricts production efficiency. In addition, when the resin matrix melt index is low, its processing temperature (usually >200°C) overlaps with the decomposition temperature of the peroxide (such as DCP half-life of 1 minute corresponds to 175°C), further exacerbating the risk of pre-cross-linking.

[0003] Taking the laminated glass industry as an example, traditional non-cross-linked PVB films need to be laminated for a long time of 3 to 4 hours under high pressure (1.3MPa) and high temperature (130-135°C), which has defects such as high equipment cost, high energy consumption, and low efficiency. At the same time, the PVB film has weak adhesion to the glass interface, poor water barrier performance, and insufficient heat resistance, making it difficult to be compatible with intelligent devices such as dimming films and display screens. In contrast, cross-linked EVA films have excellent water barrier properties, heat resistance, and intelligent compatibility based on properties such as transmittance and haze similar to PVB, and can simplify the lamination process through low-temperature cross-linking formulas (such as below 120°C), eliminating the high-pressure process. However, during the preparation of EVA films, the composite system of low melt index resin and cross-linking agent is very easy to trigger a pre-cross-linking reaction due to local overheating during extrusion, resulting in screw clogging and difficulty in achieving continuous production.

[0004] In the prior art, the main solutions to the pre-crosslinking problem include: 1) precisely controlling the molding temperature to inhibit the decomposition of the crosslinking agent, but due to the limitations of the temperature control accuracy of the equipment, it is difficult to completely avoid local overheating; 2) microencapsulating the crosslinking agent (such as patent CN114573960B), or using a composite crosslinking agent system (such as patent CN106281122B) to delay the crosslinking reaction. However, the microencapsulation technology is complex and may introduce interface defects, and the synergistic stability of the composite crosslinking agent is insufficient, and it still cannot meet the high stability processing requirements under the low melt index resin system. Therefore, the development of a technical solution that effectively inhibits pre-crosslinking during the extrusion process while ensuring the controllable crosslinking performance of the film has become a key issue that needs to be broken through in this field. Summary of the Invention

[0005] In order to make up for the shortcomings of the existing technology, the present invention provides a method for preparing a thin film material. This method can effectively prevent the base material from cross-linking during the high-temperature film forming process, clogging the die head, and preventing continuous production, thereby affecting the film production efficiency. This method is particularly suitable for the preparation of thin film materials with a low melt index resin as the base resin.

[0006] The technical solution adopted by the present invention to solve the problems of the prior art is:

[0007] According to one aspect of the present application, a method for preparing a thin film material is provided, comprising:

[0008] (S1) forming a base film: mixing a base material and adding it to a forming device to form a base film, wherein the base material comprises a base resin and an optional first cross-linking agent, wherein when the base material comprises the first cross-linking agent, the first cross-linking agent accounts for no more than 0.1% by mass of the base resin;

[0009] (S2) Adding a second cross-linking agent: adding a second cross-linking agent to the base film to form a thin film material.

[0010] Furthermore, the matrix material does not contain a first cross-linking agent.

[0011] Furthermore, the base material in step (S1) further includes other auxiliary agents, and / or step (S2) further includes adding other auxiliary agents, and the other auxiliary agents and the second cross-linking agent are added simultaneously or separately.

[0012] Furthermore, the other auxiliary agents are selected from any one or more of tackifiers, light stabilizers, ultraviolet absorbers, antioxidants, co-crosslinking agents, colorants, light conversion agents, plasticizers, and flame retardants.

[0013] Furthermore, the mass ratio of the base resin to the other additives is 100:(0.01-10), preferably 100:(0.5-5).

[0014] Furthermore, the melt index of the matrix resin at 190°C and a load of 2.16 kg is not more than 50 g / 10 min, preferably not more than 10 g / 10 min, more preferably not more than 4 g / 10 min, and most preferably not more than 0.1 g / 10 min; preferably, the matrix resin is selected from any one or more of ethylene autopolymers, ethylene-α-olefin copolymers, ethylene-α-olefin-non-conjugated diene polymers, ethylene-aromatic hydrocarbon copolymers, and ethylene-polar monomer copolymers; preferably, the matrix resin is selected from one or more of low-density polyethylene, medium-density polyethylene, ultra-low-density polyethylene, ethylene-α-olefin copolymers, ethylene-vinyl acetate, and ethylene-vinyl alcohol copolymers.

[0015] Furthermore, the matrix resin is a propylene-based polymer, wherein the mass fraction of propylene is greater than 50%; preferably, the melt index of the propylene polymer at 230°C and 2.16 kg load is 0.5 to 20 g / 10 min; preferably, the propylene-based polymer includes a propylene homopolymer, a copolymer of propylene and ethylene or α-olefin.

[0016] Furthermore, the base resin is a butene-based polymer, selected from at least one of butene-1 homopolymer, copolymer of butene-1 and ethylene or C3-C20 α-olefin, isobutylene copolymer, and butadiene homopolymer.

[0017] Furthermore, the matrix resin is polyvinyl butyral, the acetal value of which is 78% to 85%, and the hydroxyl value of which is 18% to 20%.

[0018] Furthermore, the molding equipment is a tape casting molding equipment or a calendering molding equipment.

[0019] Furthermore, the molding temperature is 80-200°C.

[0020] Furthermore, in step S2, the method of adding the second cross-linking agent is selected from coating method, spraying method, dipping method or laminating method.

[0021] Furthermore, in step (S2), the second cross-linking agent is selected from at least one of an organic peroxide cross-linking agent, a non-peroxide cross-linking agent and an inorganic peroxide cross-linking agent.

[0022] Furthermore, the second cross-linking agent is selected from an organic peroxide cross-linking agent, and the one-minute half-life temperature of the second cross-linking agent is lower than 190°C; further preferably, the one-minute half-life temperature of the second cross-linking agent is lower than 180°C; further preferably, the one-minute half-life temperature of the second cross-linking agent is lower than 170°C; further preferably, the one-minute half-life temperature of the second cross-linking agent is lower than 160°C; further preferably, the one-minute half-life temperature of the second cross-linking agent is lower than 150°C; most preferably, the one-minute half-life temperature of the second cross-linking agent is lower than 140°C.

[0023] Further, the second cross-linking agent is selected from di-tert-butyl peroxide, di-tert-amyl peroxide, tert-butyl peroxide isopropyl benzene, diisopropyl peroxide, 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, tert-hexyl peroxide-2-ethylhexyl carbonate, tert-butyl peroxide isopropyl carbonate, tert-butyl peroxide isobutyl carbonate, tert-amyl peroxide isopropyl carbonate, tert-Amyl peroxyisobutyl carbonate, tert-Butyl peroxy-2-ethylhexanoate, tert-Amyl peroxy-2-ethylhexanoate, tert-Butyl peroxyisobutyrate, tert-Amyl peroxyisobutyrate, tert-Butyl peroxy-3,5,5-trimethylhexanoate, tert-Amyl peroxy-3,5,5-trimethylhexanoate, 2,5-Dimethyl-2,5-bis(benzoylperoxy)-hexane, 2,5-Dimethyl-2,5-bis-(2-ethylhexanoylperoxy)-hexane, 1,1,3,3-Tetramethylbutyl peroxy-2-ethylhexanoate Ester, tert-butyl peroxypivalate, tert-amyl peroxypivalate, tert-butyl peroxyneoheptanoate, tert-butyl peroxide neodecanoate, tert-amyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-isopropylphenyl peroxyneoheptanoate, α-isopropylphenyl peroxyneodecanoate, 1,1-dimethyl-3-hydroxybutyl peroxyneodecanoate, dibenzoyl peroxide, dilauroyl peroxide, didecanoyl peroxide, succinyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 1, Any one or more of 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-butyl peroxybenzoate, tert-amyl peroxybenzoate, tert-butyl peroxyacetate, and tert-amyl peroxyacetate.

[0024] Furthermore, the added mass of the second cross-linking agent is 0.001 to 5% of the mass of the base material.

[0025] Furthermore, step (S3) pre-crosslinking treatment is included. Preferably, the pre-crosslinking treatment is selected from at least one of thermal crosslinking, radiation crosslinking, UV crosslinking, microwave crosslinking or laser crosslinking; preferably, the pre-crosslinking degree of the film material is 0 to 70%, preferably 5 to 30%.

[0026] Furthermore, at least one side surface of the film material has regular or irregular patterns.

[0027] According to a second aspect of the present application, a thin film material is provided. The thin film material is a single layer or a multilayer, and at least one layer of the thin film material is prepared by the preparation method described in the first aspect.

[0028] According to a third aspect of the present application, there is provided a use of the thin film material of the second aspect, wherein the thin film material is used for encapsulation of automotive glass, architectural glass, electronic devices or photovoltaic modules.

[0029] The beneficial effects of the present invention mainly lie in that the cross-linking agent is added in trace amounts or not at all before high-temperature forming, and is mainly added in step (S2) after high-temperature forming, which can avoid cross-linking during the high-temperature forming process. When the cross-linking agent is directly mixed into the matrix material in one step in the traditional process, the high-temperature forming process may cause the cross-linking agent to react prematurely (such as decomposition of organic peroxides), resulting in excessive cross-linking of the base film and degradation of subsequent processing performance. The step (S1) of the present application contains a trace amount or no first cross-linking agent, and the second cross-linking agent is mainly added through step (S2), which can avoid the risk of pre-cross-linking in the forming stage, avoid the formation of hard particles or coke clogging the equipment due to local cross-linking, thereby improving production efficiency, reducing the frequency of shutdown cleaning, and extending the life of the equipment (such as an extruder). The distribution of the cross-linking agent is controllable: by post-addition methods such as coating and spraying, the cross-linking agent can be accurately distributed on the surface of the base film or in a specific layer (such as the interface layer of a multilayer film) to achieve local cross-linking strengthening and avoid embrittlement of the overall material. DETAILED DESCRIPTION

[0030] To make the objectives, technical solutions, and advantages of the embodiments of the present invention more clear, the technical solutions of the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a portion of the embodiments of the present invention, not all of them. Based on the described embodiments of the present invention, all other embodiments derived by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0031] Unless otherwise defined, technical or scientific terms used in the present disclosure shall have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs.

[0032] In conventional film materials, at the crosslinker content required to achieve a predetermined degree of crosslinking, during the extrusion process, especially at high temperatures, a chain reaction initiated by the crosslinker forms micro-crosslinked regions in the melt, further increasing melt viscosity, hindering flow, and exacerbating equipment clogging, resulting in low film production efficiency. Accumulation of gel particles leads to frequent shutdowns for die cleaning or filter replacement, reducing equipment utilization. This application proposes a novel film preparation method that can precisely control the crosslinking reaction.

[0033] According to one aspect of the present application, a method for preparing a thin film material is provided, comprising: (S1) forming a base film: mixing a base material and adding it to a forming device to form a base film, wherein the base material comprises a base resin and an optional first cross-linking agent, wherein, when the base material comprises the first cross-linking agent, the first cross-linking agent accounts for no more than 0.1% of the mass of the base resin, as measured by mass percentage; (S2) adding a second cross-linking agent: adding the second cross-linking agent to the base film to form a thin film material. By adding a trace amount of or no first cross-linking agent before forming the base film, and independently adding a major amount of the second cross-linking agent after forming the base film (rather than mixing it into the base material), the following can be achieved: (1) avoiding pre-cross-linking: in conventional processes, when a predetermined amount of cross-linking agent in a formula system is directly mixed into the base material in a one-step process, the high-temperature forming process may trigger a premature reaction of the cross-linking agent (such as decomposition of an organic peroxide), resulting in excessive cross-linking of the base film and deterioration of subsequent processing performance. The present application contains a trace amount or no first cross-linking agent in step (S1), and the second cross-linking agent is mainly added through step (S2), which can avoid a large amount of cross-linking in advance during the high-temperature molding process (S1), eliminate gel particles caused by pre-cross-linking, avoid the formation of hard particles or coke blocks due to local cross-linking, and reduce the risk of blockage of the screw and die. (2) The distribution of the cross-linking agent is controllable: the cross-linking agent is mainly added through coating, spraying, etc., and the cross-linking agent can be accurately distributed on the surface of the base film or in a specific layer (such as the interface layer of a multi-layer film), achieving local cross-linking reinforcement and avoiding embrittlement of the overall material.

[0034] In a preferred embodiment of the present application, the mass content ratio of the cross-linking agent compared to the base resin is less than 0.01% by mass. Further, the mass content ratio of the cross-linking agent compared to the base resin is less than 0.001%. Further, the base material does not contain a first cross-linking agent. When the content of the first cross-linking agent in the base material is ≤0.01% (further preferably ≤0.001%, more preferably not added at all), during the high-temperature molding process (such as a casting or calendering temperature of 80 to 200°C), the decomposition amount of the cross-linking agent is extremely low or even zero, and the cross-linking degree of the base film approaches 0%, thereby eliminating gel particles and coke, reducing the risk of equipment blockage, and extending the maintenance cycle of components such as the screw and die head; maintaining the melt fluidity of the base film and avoiding difficulties in thermoforming due to pre-cross-linking (such as uneven thickness and surface defects).

[0035] In some embodiments, the matrix material in step (S1) further includes other additives.

[0036] In some embodiments, the step (S2) further includes adding other additives, which can be added simultaneously with the second cross-linking agent or added separately. Specifically, on the one hand, process adaptability is considered to adapt to different production scenarios: high-temperature sensitive additives can be added later until the S2 low-temperature stage to avoid decomposition; additives that require pre-dispersion can be added during the S1 matrix mixing stage. On the other hand, the synergistic effect of the additive properties is considered, such as the simultaneous addition of antioxidants and cross-linking agents to form a synergistic stabilization system (such as the combination of phenolic antioxidants and peroxide cross-linking agents).

[0037] In some embodiments, the other additives are selected from any one or more of tackifiers, light stabilizers, UV absorbers, antioxidants, cross-linking agents, light conversion agents, colorants, plasticizers, and flame retardants to improve the light stability, thermal stability, adhesion, processability and other properties of the film material.

[0038] In some embodiments, the auxiliary crosslinking agent is selected from triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, tris(2-hydroxyethyl)isocyanurate triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, ethoxylated glycerol triacrylate, propoxylated glycerol triacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, trimethylolpropane tetraacrylate, ditrimethylolpropane tetraacrylate, ditrimethylolpropane tetramethacrylate, propoxylated pentaerythritol tetraacrylate. At least one of ester, 2,4,6-tris(2-propenyloxy)-1,3,5-triazine, tricyclodecane dimethanol diacrylate, propoxylated neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, 2-butyl-2-ethyl-1,3-propanediol diacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate and polyethylene glycol dimethacrylate; the above-mentioned co-crosslinking agent selected in this application and other components work synergistically to further promote the crosslinking reaction of the raw material molecules, so that the thin film material has a higher degree of crosslinking, which meets the long-term reliability of the photovoltaic module.

[0039] The addition of a tackifier can improve the bonding performance between the film and the substrate. In some embodiments, the tackifier is selected from at least one of a silane coupling agent, a silane-modified ethylene-vinyl acetate copolymer, a silane-modified polyolefin elastomer, a silane-modified ethylene-methyl acrylate copolymer, a silane-modified ethylene-acrylic acid copolymer, and a silane-modified polymethyl methacrylate.

[0040] In some embodiments, the silane coupling agent is selected from at least one of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltriperoxide tert-butylsilane, vinyltriacetoxysilane, vinyltris(β-methoxyethoxy)silane, γ-aminopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethylsilane and 3-aminopropyltrimethylsilane.

[0041] In some embodiments, the UV absorber includes one or more of 2,4-di-tert-butylphenyl 3,5-di-tert-butyl-4-hydroxybenzoate, hexadecyl 3,5-di-tert-butyl-4-hydroxybenzoate, 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl-5-(octyloxy)-phenol, 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, and 2,4-dihydroxybenzophenone.

[0042] In some embodiments, the light stabilizer includes bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, 1-(methyl)-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate, 3,5-di-tert-butyl-4-hydroxy-benzoic acid hexadecyl ester, bis-2,2,6,6-tetramethylpiperidinol sebacate, tris(1,2,2,6,6-pentamethyl-4-piperidinyl) phosphite, bis-2,2,6,6-tetramethylpiperidinol sebacate, bis-1-decyloxy-2,2,6,6-tetramethylpiperidin-4-ol sebacate. One or more of a polymer of ester, succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediene[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)1,6-hexanediamine, and morpholine-2,4,6-trichloro-1,3,5-triazine.

[0043] In some embodiments, the antioxidant includes one or more of didodecenyl-p-cresol, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), and 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid.

[0044] In some embodiments, the film composite material further comprises a plasticizer; the mass ratio of the plasticizer to the matrix resin is 15 to 30:100. In a preferred embodiment, the plasticizer is selected from any one or more of dimethoxyethylene glycol phthalate, tricresyl phosphate, dipropylene glycol phthalate, triethylene glycol dipelargonate, and coumarone-indene resin. The addition of the plasticizer helps to lower the glass transition temperature of the matrix resin. Preferably, the mass ratio of the plasticizer to the matrix resin is controlled within the above range, which helps to improve the acoustic damping properties of the matrix resin, allowing it to maintain good flexibility and viscoelasticity over a wider temperature range, thereby helping to enhance the matrix resin's ability to absorb and attenuate sound waves.

[0045] In some embodiments, the photoconversion agent is selected from organic photoconversion agents, inorganic photoconversion agents and organic-inorganic hybrid photoconversion agents, preferably organic photoconversion agents, and the organic photoconversion agent is preferably benzotriazole, triazine, benzophenone, carbazole, quinoxaline, benzimidazole and triphenylamine and their derivatives.

[0046] In some embodiments, the colorant is selected from titanium dioxide, carbon black, organic dyes, and the like.

[0047] In a typical embodiment, the mass ratio of the base resin to the other additives is 100:

[0048] (0.01-10), preferably 100: (0.5-5). When the content of other additives is less than 0.01 parts, their functionality (such as viscosity enhancement, anti-aging, flame retardancy, etc.) cannot be effectively exerted. When the content of other additives exceeds 10 parts, it will cause the following problems: Deterioration of dispersibility: Excessive other additives are difficult to disperse evenly in the matrix resin, forming agglomerated particles, resulting in increased surface roughness of the film and decreased optical properties. It will also cause deterioration of processing performance:

[0049] High content of plasticizer or flame retardant will significantly reduce the viscosity of the resin melt, resulting in film thickness fluctuations of >±20% during casting or extrusion molding, and even film breakage.

[0050] In some specific embodiments, the mass ratio of the tackifier, UV absorber, antioxidant, cross-linking agent, and light conversion agent to the base resin is 0-5% by mass, and the mass ratio of the colorant to the base resin is 0-40% by mass.

[0051] In a typical embodiment, the melt index of the matrix resin at 190°C and a load of 2.16 kg does not exceed 50 g / 10 min, preferably does not exceed 10 g / 10 min, more preferably does not exceed 4 g / 10 min, and most preferably does not exceed 0.1 g / 10 min. Preferably, the matrix resin is selected from any one or more of ethylene autopolymers, ethylene-α-olefin copolymers, ethylene-α-olefin-non-conjugated diene polymers, ethylene-aromatic hydrocarbon copolymers, and ethylene-polar monomer copolymers. Preferably, the matrix resin is selected from one or more of low-density polyethylene, medium-density polyethylene, ultra-low-density polyethylene, ethylene-α-olefin copolymers, ethylene-vinyl acetate, and ethylene-vinyl alcohol copolymers. Low melt index resins have high molecular weight, long molecular chains, and high melt viscosity. They exhibit higher melt strength during extrusion film formation (such as blown film or cast film), and can effectively resist necking or film breakage during stretching. The long molecular chains of low-melt-index resins are more tightly entangled in the molten state, making it easier for crosslinkers (such as peroxides and silanes) to react and form a uniform and dense three-dimensional network structure, significantly improving the crosslinking degree and mechanical properties of the film. Furthermore, the high-viscosity melt inhibits localized accumulation or migration of the crosslinker during processing, avoiding crosslink network defects caused by uneven concentration. The high molecular weight of the low-melt-index resin can partially replace the reinforcing effect of the crosslinker, reducing the amount of crosslinker added while achieving equivalent mechanical properties, thereby lowering formulation costs.

[0052] In some specific embodiments, the matrix resin is a propylene-based polymer, wherein the mass fraction of propylene is greater than 50%; preferably, the melt index of the propylene polymer at 230°C and a load of 2.16 kg is 0.5 to 20 g / 10 min; preferably, the propylene-based polymer includes a propylene homopolymer, a copolymer of propylene and ethylene or an α-olefin. When the mass fraction of propylene is greater than 50%, the propylene unit in the polymer backbone is dominant, giving the material high rigidity and heat resistance. At the same time, by introducing ethylene or α-olefin (such as 1-butene, 1-hexene) comonomers, the crystallinity can be controlled to avoid film embrittlement. The lower limit control of the propylene polymer (MI ≥ 0.5 g / 10 min) ensures that the melt fluidity meets the requirements of the casting or extrusion process, and avoids uneven film thickness or excessive equipment pressure due to excessively high melt viscosity (MI < 0.5). At the same time, the upper limit control (MI ≤ 20 g / 10 min) prevents the melt viscosity from being too low, resulting in insufficient molecular chain orientation, and the difference in longitudinal / transverse tensile strength of the film is greater than 50%.

[0053] In some specific embodiments, the matrix resin is a butene-based polymer selected from at least one of butene-1 homopolymer, copolymers of butene-1 and ethylene or C3-C20 α-olefins, isobutylene copolymers, and butadiene homopolymers. The crystalline and amorphous regions of the butene-1 homopolymer are alternately distributed, and the crosslinking agent preferentially penetrates the amorphous region, forming a locally highly crosslinked network while retaining a low-crosslinked structure internally, giving the film both surface wear resistance and overall flexibility. Butene-1 copolymers can regulate crystallinity. By introducing ethylene or α-olefins (such as 1-hexene), the crystallinity can be reduced to 20-35%, balancing rigidity and toughness; at the same time, interfacial adhesion is enhanced:

[0054] The copolymer's increased amorphous region proportion and surface energy enhance its bonding strength to polar materials (such as glass and metal). Isobutylene copolymers possess high damping properties. The flexible isobutylene segments and crosslinking points in the molecular chain form a network structure, resulting in a film with a damping factor ≥ 0.3 over a wide temperature range (-50 to 100°C), making it suitable for automotive shock and sound insulation interlayers. Furthermore, the copolymer exhibits excellent airtightness: its permeability to gases (such as O2 and H2O) is extremely low, making it suitable for use in high-barrier packaging films.

[0055] In some preferred embodiments, the base resin is selected from polyvinyl butyral; more preferably, the acetal value of the polyvinyl butyral is 78% to 85%, and the hydroxyl value is 18% to 20%. The present application controls the hydroxyl value content and acetal value content of the PVB resin within a reasonable range, thereby reducing the water absorption rate of the PVB particles and the possibility of electrostatic adsorption and agglomeration caused by particle friction during the mixing process to reduce the performance of the material. The PVB molecular chain with an acetal value in the range of 78% to 85% has good flexibility. The introduction of acetal groups interrupts the regular hydrogen bond network of polyvinyl alcohol, giving the PVB chain segments moderate flexibility, so that the film has both toughness and tear resistance at room temperature. As a hydrophobic group, when the acetal group accounts for more than 78%, it can effectively reduce the water absorption rate of PVB and avoid interfacial stratification caused by water absorption and swelling. The technical solution of the present application retains an appropriate amount of hydroxyl groups to enhance the hydrogen bonding effect between PVB and polar substrates such as glass and metal, so that the interfacial peeling strength is high. When the hydroxyl value is ≤20%, the surface polarity of the PVB particles is moderate, and the electrostatic charge density generated by friction during the mixing process is low, which significantly reduces the risk of particle agglomeration.

[0056] In a specific embodiment, the molding equipment in (S1) is selected from a tape casting molding equipment or an extrusion molding equipment. In a specific embodiment of the present application, the molding equipment is a tape casting molding equipment, and the tape casting molding equipment includes a melt conveying system and a cooling roller group. A uniform base film surface is formed by melt casting, avoiding thickness fluctuations or surface defects caused by uneven shear force in traditional calendering processes. In another specific embodiment of the present application, the molding equipment is an extrusion molding equipment, including a single-screw extruder or a twin-screw extruder. In the range of 80 to 200°C, the matrix material (such as ethylene vinyl acetate, polyvinyl butyral) can achieve a balance between melt fluidity and thermal stability, which can not only ensure uniform extrusion of the melt, but also prevent resin decomposition or volatilization of additives at high temperatures, and is particularly suitable for multi-layer co-extrusion processes.

[0057] In a preferred embodiment of this application, the molding temperature is 80-200°C. Temperatures below 80°C can lead to insufficient melt fluidity in the base resin, which can result in incomplete base film molding or a rough surface. Temperatures above 200°C can cause thermal degradation of the resin, and additives (such as light stabilizers and antioxidants) can evaporate and become ineffective. This temperature window of 80-200°C ensures that the base film has both high moldability and material stability.

[0058] In some embodiments, (S2) the second cross-linking agent is added in a manner comprising at least one of a coating method, a spraying method, a dipping method, and a laminating method.

[0059] In some embodiments, the coating method is to apply the coating liquid of the cross-linking agent on the surface of at least one side of the base film. Preferably, the viscosity of the coating liquid is 5-1000cP, and more preferably, the viscosity of the coating liquid is 50-500cP. The viscosity of the coating liquid is within the above range, which can ensure that the coating liquid fully wets the surface of the base film and avoids shrinkage holes or pinhole defects caused by interfacial tension. At the same time, it can inhibit the vertical flow under the action of gravity, maintain the consistency of film thickness in vertical coating or high-speed roller coating, and reduce the edge thickening phenomenon. When the viscosity is too low (<50cP), the solvent flash evaporation rate is too fast, which can easily lead to Bénard convection vortex and trigger the orange peel effect; when the viscosity is too high (>500cP), the solvent diffusion coefficient decreases and the drying energy consumption increases.

[0060] In some embodiments, the coating includes but is not limited to one of roller coating, wire rod coating, slit coating, blade coating, extrusion coating or micro-gravure coating. Roller coating is the process of evenly transferring the coating to the surface of the substrate by a rotating roller, which can be divided into forward coating and reverse coating (the roller moves in the same or opposite direction as the substrate). Wire rod coating is the process of scraping a metering rod (Meyer rod) with a metal wire wrapped around the surface, and the wet film thickness is controlled by the gap between the wires. Slit coating is the process of extruding the coating from a precision slit and directly applying it to the moving substrate, and the thickness is controlled by adjusting the slit width and speed. Blade coating is the process of using a blade to scrape off excess coating on the surface of the substrate, and the coating thickness is controlled by the blade gap. Extrusion coating is the process of extruding molten coating through an extruder head and directly applying it to the surface of the substrate. Micro-gravure coating is the process of transferring the coating to the substrate after a micro-gravure roller carries the coating through the mesh, and the excess material is scraped off by a blade before being transferred to the substrate. The most suitable coating method can be selected according to the specific application scenario (substrate type, coating thickness, production efficiency, cost, etc.). Blade / slot coating requires a viscosity of 200-500 cP to resist shear thinning and ensure slot extrusion stability. Micro-gravure coating: Adapts to viscosities of 5-1000 cP, achieving nanometer-level wet film thickness control. This viscosity range allows linear control of wet film thickness from 0.5-50 μm by adjusting the coating speed.

[0061] In some embodiments, the spray coating method is to use an atomizing device to disperse the coating into tiny droplets and spray them onto the surface of the substrate. The atomizing device is selected from a spray gun or an atomizing device.

[0062] In a specific embodiment, the immersion method involves immersing the base membrane in a crosslinker solution to allow the crosslinker to adsorb onto the base membrane. The base membrane is completely immersed in the crosslinker solution at a crosslinker concentration of 5-100% by weight. A 100% crosslinker concentration, i.e., no solvent is added to the crosslinker, is achieved. The immersion time is 5 seconds to 60 minutes. In a specific embodiment, the immersion method can also be performed by adjusting the solution concentration in stages to achieve a gradient distribution of the crosslinker, thereby enhancing interfacial bonding strength.

[0063] In a specific embodiment, the coating method is to coat the additive on at least one surface of the base film, the base film has a running speed of 5-30 m / min, and a thickness deviation of <±3%.

[0064] In a specific embodiment, the coating method, spraying method, dipping method, and laminating method may be used in combination.

[0065] In some embodiments, the base film is dried after adding the second cross-linking agent, and the drying process includes hot air drying at 60-120°C for 1-60 minutes. The lower limit of the drying temperature in this application is 60°C to ensure that the mobility of the cross-linking agent molecular segments is enhanced to avoid the cross-linking degree being lower than 80% due to insufficient temperature; the upper limit is 120°C to match the glass transition temperature of most polymer base films and prevent the base film from shrinking or deforming due to overheating. When the drying time is ≥1min, the solvent volatilization rate can reach more than 95%, reducing the bubble defects inside the coating; when the time is ≤60min, excessive cross-linking is avoided to cause brittleness of the film material. Rapid drying can shorten the relaxation time of the cross-linker from liquid to solid state and inhibit phase separation caused by the migration of auxiliary agents.

[0066] In some embodiments, the second crosslinking agent in step (S2) is selected from at least one of an organic peroxide crosslinking agent, a non-peroxide crosslinking agent, and an inorganic peroxide crosslinking agent. Furthermore, the second crosslinking agent is selected from an organic peroxide crosslinking agent, and the one-minute half-life temperature of the second crosslinking agent is lower than 190°C; more preferably, the one-minute half-life temperature of the crosslinking agent is lower than 180°C; further preferably, the one-minute half-life temperature of the crosslinking agent is lower than 170°C; further preferably, the one-minute half-life temperature of the crosslinking agent is lower than 160°C; further preferably, the one-minute half-life temperature of the crosslinking agent is lower than 150°C; most preferably, the one-minute half-life temperature of the crosslinking agent is lower than 140°C. A sufficient decomposition rate can be achieved at a lower temperature (such as a 1-minute half-life at 140°C), free radicals are generated quickly, the crosslinking induction period is shortened, and production efficiency is improved. Low-temperature decomposition reduces the temperature difference between the inside and outside of the material, avoids uneven crosslinking caused by local overheating, and thus improves the mechanical properties and stability of the product; a low half-life temperature (such as 140°C) is preferred to achieve sufficient crosslinking at a lower temperature and expand the process window.

[0067] In a specific embodiment, the second cross-linking agent is a molecule having multiple ethylenically unsaturated groups, which can promote cross-linking of the polymer to achieve a higher degree of cross-linking. The second cross-linking agent is preferably an organic peroxide cross-linking agent; preferably, the cross-linking agent is selected from di-tert-butyl peroxide, di-tert-amyl peroxide, tert-butyl isopropyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, tert-Hyl peroxy-2-ethylhexyl carbonate, tert-Butyl peroxyisopropyl carbonate, tert-Butyl peroxyisobutyl carbonate, tert-Amyl peroxyisopropyl carbonate, tert-Amyl peroxyisobutyl carbonate, tert-Butyl peroxy-2-ethylhexanoate, tert-Amyl peroxy-2-ethylhexanoate, tert-Butyl peroxyisobutyrate, tert-Amyl peroxyisobutyrate, tert-Butyl peroxy-3,5,5-trimethylhexanoate, tert-Amyl peroxy-3,5,5-trimethylhexanoate, 2,5-Dimethyl-2,5-bis(benzoylperoxy)-hexane, 2,5-Dimethyl-2,5-bis-(2-ethylhexanoate) Hexanoyl peroxide)-hexane, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-butyl peroxypivalate, tert-amyl peroxypivalate, tert-butyl peroxyneoheptanoate, tert-butyl peroxide neodecanoate, tert-amyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-cumyl peroxyneoheptanoate, α-cumyl peroxyneodecanoate, 1,1-dimethyl-3-hydroxybutyl peroxyneodecanoate, dibenzoyl peroxide, dilauroyl peroxide, didecanoyl peroxide, succinyl peroxide, Any one or more of 3,5,5-trimethylhexanoyl peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-butyl peroxybenzoate, tert-amyl peroxybenzoate, tert-butyl peroxyacetate, and tert-amyl peroxyacetate.

[0068] In some specific embodiments, when the matrix material comprises a first crosslinking agent, the first crosslinking agent is selected from di-tert-butyl peroxide, di-tert-amyl peroxide, tert-butyl isopropyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, tert-hexyl peroxide-2-ethylhexyl carbonate, tert-butyl peroxide isopropyl carbonate, isobutyl peroxide tert-Butyl peroxide, tert-Amyl peroxyisopropyl carbonate, tert-Amyl peroxyisobutyl carbonate, tert-Butyl peroxy-2-ethylhexanoate, tert-Amyl peroxy-2-ethylhexanoate, tert-Butyl peroxyisobutyrate, tert-Amyl peroxyisobutyrate, tert-Butyl peroxy-3,5,5-trimethylhexanoate, tert-Amyl peroxy-3,5,5-trimethylhexanoate, 2,5-Dimethyl-2,5-bis(benzoylperoxy)-hexane, 2,5-Dimethyl-2,5-bis-(2-ethylhexanoylperoxy)-hexane, 1-Ethylhexanoate-2-Peroxy ,1,3,3-tetramethylbutyl peroxide, tert-butyl peroxypivalate, tert-amyl peroxypivalate, tert-butyl peroxyneoheptanoate, tert-butyl peroxide neodecanoate, tert-amyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-isopropylphenyl peroxyneoheptanoate, α-isopropylphenyl peroxyneodecanoate, 1,1-dimethyl-3-hydroxybutyl peroxyneodecanoate, dibenzoyl peroxide, dilauroyl peroxide, didecanoyl peroxide, succinyl peroxide, 3,5,5-trimethyl peroxide Any one or more of hexanoyl, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-butyl peroxybenzoate, tert-amyl peroxybenzoate, tert-butyl peroxyacetate, and tert-amyl peroxyacetate.

[0069] In some embodiments, the added mass of the second cross-linking agent is 0.001 to 5% of the mass of the matrix material. Specifically, 0.001%, 0.005%, 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range of any two values. Too little additive may lead to weakened adhesion, while too much may cause side effects such as slippage on the film surface, affect the packaging performance, or increase unnecessary costs. The above proportion is conducive to the formation of appropriate free radicals in the pre-cross-linking process of the film, which can not only strengthen the cross-linking of the molecular chains, but also retain enough active sites to form a strong bond with the laminated components such as glass during the lamination stage.

[0070] In some embodiments, step (S3) pre-crosslinking treatment is also included. Preferably, the pre-crosslinking treatment is selected from at least one of thermal crosslinking, radiation crosslinking (such as electron beam or gamma ray), ultraviolet crosslinking, microwave crosslinking or laser crosslinking. Through the pre-crosslinking technology, a controllable primary crosslinking network is formed inside the material, which not only retains the plasticity required for subsequent processing, but also gives the material preliminary mechanical strength and environmental resistance. Thermal crosslinking induces a crosslinking reaction by controlling the temperature (preferably 80-200°C) and time (1-60 minutes). Radiation crosslinking uses a high-energy particle beam generated by an electron accelerator, which can achieve rapid crosslinking at room temperature. Preferably, the irradiation voltage of the electron beam irradiation is 350-450kv, and the irradiation dose is 8-12KGY. The irradiation voltage of electron beam irradiation is 350kV, 380kV, 400kV, 420kV, 450kV or a range consisting of any two of them, and the irradiation dose is 8KGY, 9KGY, 10KGY, 11KGY, 12KGY or a range consisting of any two of them. The above irradiation voltage and irradiation dose are conducive to providing a more moderate energy level, which is sufficient to excite the double bonds of the first auxiliary agent to produce free radicals and achieve pre-crosslinking of the film without excessively destroying the second auxiliary agent, so that more sufficient effective chemical bonds are formed between the film and the glass during lamination, thereby significantly enhancing the stability of the packaging structure and the long-term reliability of the photovoltaic module. Ultraviolet crosslinking excites the photoinitiator through a light source with a specific wavelength (such as 254nm or 365nm) to achieve selective crosslinking in a local area. Microwave crosslinking uses polar molecular vibration to generate heat, and has the characteristics of high energy utilization and uniform crosslinking. Laser crosslinking uses pulsed laser for precise crosslinking in micro areas.

[0071] In a preferred embodiment, the pre-crosslinking degree of the film material is 0 to 70%, preferably 5 to 30%. The pre-crosslinking degree is defined as the proportion of crosslinked bonds formed in the material, and is determined by the gel content method or the swelling method. When the pre-crosslinking degree is lower than 5%, the mechanical strength of the material is limited, and deformation is prone to occur during processing; when the pre-crosslinking degree reaches 5-30%, the material exhibits an excellent balance between processability and structural stability; if it exceeds 70%, the brittleness of the material increases significantly, making it difficult to perform subsequent secondary operations such as lamination. Gel content is an indicator of the degree of crosslinking of the film. Accurately measure 0.8 to 1 g of the film sample, wrap it with a 200 mesh copper mesh, and place it in slightly boiling xylene for extraction for 12 hours, during which the solvent is replaced twice; remove the copper mesh and place it in an oven to dry to constant weight, and calculate the gel content according to the requirements of GB29848-2018.

[0072] In some embodiments, at least one side of the film material comprises a regular or irregular pattern. Preferably, the pattern comprises: a first pattern extending substantially along a first direction; a second pattern extending substantially along a second direction; the first and second directions intersecting at a predetermined angle, the predetermined angle being greater than 0° and less than 180°; and the surface pattern comprises at least one first pattern and at least one second pattern. Furthermore, the film body has a thickness of 0.3-2.0 mm, the first pattern has a length of 1-5 mm and a width of 0.05-3 mm, and the second pattern has a length of 1-5 mm and a width of 0.05-3 mm.

[0073] According to a second aspect of the present application, a thin film material is provided. The thin film material is a single layer or a multilayer, and at least one layer of the thin film material is prepared by the preparation method described in the first aspect.

[0074] According to a third aspect of the present application, there is provided a use of the thin film material of the second aspect, wherein the thin film material is used for encapsulation of automotive glass, architectural glass, electronic devices or photovoltaic modules.

[0075] The beneficial effects of the present application will be further illustrated below with reference to examples.

[0076] Example 1

[0077] 100 parts by mass of EVA resin with a melt index of 6 g / 10 min, 0.8 parts by mass of tackifier A172, and 0.3 parts by mass of triallyl isocyanurate were added to an extruder at a temperature of 90° C. and extruded through a T-die to form a base film. 0.012 parts by mass of tert-butyl peroxycarbonate-2-ethylhexyl ester relative to the base material was coated on the base film and cooled to obtain a film material.

[0078] Example 2

[0079] A PVB resin with a melt index of 2 was added to an extruder at 200°C and extruded through a T-die to form a base film. 0.005 parts by mass of 2-ethylhexyl tert-butyl peroxycarbonate relative to the base material was sprayed onto the base film, and the film material was cooled to produce a film material. An EVA film, the film material, and the EVA film were then rolled together to produce a composite film material.

[0080] Example 3

[0081] 100 parts by mass of PVB resin with a melt index of 1 and 10 parts by mass of triethylene glycol di(2-ethylbutyrate) as a base material were added to an extruder at 180°C and extruded through a T-die to form a base film. 0.005 parts of tert-butyl peroxycarbonate-2-ethylhexyl was sprayed onto the base film and cooled to produce a film material. A POE film, the film material, and the POE film were then rolled together to produce a composite film material.

[0082] Example 4

[0083] 100 parts by mass of POE resin with a melt index of 10 g / 10 min and 2 parts by mass of silane coupling agent as a base material were added to an extruder at a temperature of 70° C. and extruded through a T-die to form a base film. 0.008 parts by mass of tert-butyl peroxycarbonate-2-ethylhexyl ester relative to the base material was coated on the base film and cooled to obtain a film material.

[0084] Example 5

[0085] 100 parts by mass of PVB resin with a melt index of 4, 0.8 parts by mass of A172 tackifier, 5 parts by mass of dioctyl phthalate, and 25 parts by mass of dimethoxyethylene phthalate as matrix materials were added to an extruder at an extruder temperature of 180°C. The base film was formed by extrusion through a T-die. The base film was passed through an ethanol solution of 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane at a speed of 15 m / min and rolled up at room temperature to obtain the base film.

[0086] Example 6

[0087] 100 parts by mass of PVB resin with a melt index of 0.5, 0.8 parts by mass of A172 tackifier, and 30 parts by mass of dipropylene glycol phthalate as a base material were added to an extruder at an extruder temperature of 190° C. and extruded through a T-die to form a base film. 0.01 parts by mass of tert-butyl peroxycarbonate-2-ethylhexyl ester relative to the base material was coated on the base film and cooled to obtain a film material.

[0088] Example 7

[0089] 100 parts of POE resin with a melt index of 4 g / 10 min, 0.5 parts by mass of A174 tackifier, and 0.2 parts by mass of triallyl isocyanurate as a cross-linking agent are used as base material 1; 100 parts by mass of PVB resin, 0.8 parts by mass of A172 tackifier, and 2 parts by mass of triethylene glycol dipelargonate are used as base material 2; 100 parts of POE resin with a melt index of 4 g / 10 min, 0.5 parts by mass of A174 tackifier, and 0.2 parts by mass of triallyl isocyanurate as a cross-linking agent are added into an extruder respectively, the extruder temperature is 200° C., and a base film is formed by extrusion through a T-die. 0.01 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester relative to the base material is coated on the base film, and the film material is obtained by cooling.

[0090] Example 8

[0091] Different from Example 1, the base film of the film material has a well-shaped pattern.

[0092] Example 9

[0093] Different from Example 1, the melt index of the EVA resin of the film material is 20 g / 10 min.

[0094] Example 10

[0095] The difference from Example 1 is that the matrix material further includes 0.1 parts by weight of 2-ethylhexyl tert-butyl peroxycarbonate.

[0096] Example 11

[0097] The difference from Example 1 is that the matrix material further includes 0.01 parts by weight of 2-ethylhexyl tert-butyl peroxycarbonate.

[0098] Example 12

[0099] The difference from Example 1 is that 100 parts by mass of EVA resin with a melt index of 6 g / 10 min and 0.8 parts by mass of tackifier A172 are added to the extruder as the base material. The extruder temperature is 90°C and the base film is formed by extrusion through a T-die. 0.012 parts by mass of tert-butyl peroxycarbonate-2-ethylhexyl ester and 0.3 parts by mass of triallyl isocyanurate relative to the base material are sequentially coated on the base film and cooled.

[0100] Example 13

[0101] Different from Example 1, the base material to which the second crosslinking agent has been added is cooled and transferred to an electron irradiation device with an energy of 80keV for electron irradiation with an intensity of 30kGy. After irradiation, the base material is rolled up to obtain a pre-crosslinked film material with a pre-crosslinking degree of 28%.

[0102] Comparative Example 1

[0103] 100 parts by mass of EVA resin with a melt index of 6 g / 10 min, 0.8 parts by mass of tackifier A172, 0.3 parts by mass of triallyl isocyanurate, and 0.012 parts by mass of 2-ethylhexyl tert-butyl peroxycarbonate were added as matrix materials into an extruder at a temperature of 90° C. and extruded through a T-die to form a film material.

[0104] Comparative Example 2

[0105] The difference from Example 1 is that the base material further includes 0.2 parts by weight of 2-ethylhexyl tert-butyl peroxycarbonate.

[0106] Performance testing:

[0107] (1) Processing conditions: During the processing of Examples 1-13 and Comparative Examples 1-2, observe whether die blockage occurs and whether gel particles accumulate.

[0108] (2) The film materials prepared in Examples 1-13 and Comparative Examples 1-2 were laminated to glass, and the initial peel strength between the glass and the film was measured on a tensile testing machine according to the test method of standard GB / T2790.

[0109] The properties of the thin film materials prepared in Examples 1 to 13 and Comparative Examples 1-2 were measured, and the results are shown in Table 1.

[0110] Table 1

[0111]

[0112] As can be seen from Table 1, the thin film material of the present invention does not add or adds a trace amount of the first cross-linking agent in step (S1), and the second cross-linking agent is added after high-temperature molding. This can avoid cross-linking during the high-temperature molding process, avoid the formation of hard particles or coke due to local cross-linking to block the equipment, reduce the frequency of shutdown cleaning, and extend the life of the equipment; avoid local cross-linking differences caused by uneven temperature distribution during the molding process, and have better bonding performance with glass.

[0113] The above embodiments are only intended to help understand the method of the present invention and its core concept. It should be noted that, without departing from the principles of the present invention, a number of improvements and modifications may be made to the present invention by those skilled in the art, and such improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a thin film material, characterized in that: include: (S1) Base film forming: mixing a base material and adding it into a forming device to form a base film, wherein the base material comprises a base resin and an optional first cross-linking agent, wherein when the base material comprises the first cross-linking agent, the mass proportion of the first cross-linking agent to the base resin is not higher than 0.1% by mass; (S2) Adding a second cross-linking agent: adding a second cross-linking agent to the base film to form a thin film material.

2. The preparation method according to claim 1, characterized in that The matrix material does not include a first cross-linking agent.

3. The preparation method according to claim 1 or 2, characterized in that The base material in step (S1) further comprises other auxiliary agents, and / or step (S2) further comprises adding other auxiliary agents, wherein the other auxiliary agents and the second cross-linking agent are added simultaneously or separately; Preferably, the other auxiliary agents are selected from any one or more of tackifiers, light stabilizers, ultraviolet absorbers, antioxidants, co-crosslinking agents, colorants, light conversion agents, plasticizers, and flame retardants; Preferably, the mass ratio of the base resin to the other additives is 100:(0.01-10), preferably 100:(0.5-5).

4. The preparation method according to claim 1, characterized in that The melt index of the matrix resin at 190°C and a load of 2.16 kg does not exceed 50 g / 10 min, preferably does not exceed 10 g / 10 min, more preferably does not exceed 4 g / 10 min, and most preferably does not exceed 0.1 g / 10 min; preferably, the matrix resin is selected from any one or more of ethylene autopolymers, ethylene-α-olefin copolymers, ethylene-α-olefin-non-conjugated diene polymers, ethylene-aromatic hydrocarbon copolymers, and ethylene-polar monomer copolymers; preferably, the matrix resin is selected from one or more of low-density polyethylene, medium-density polyethylene, ultra-low-density polyethylene, ethylene-α-olefin copolymers, ethylene-vinyl acetate, and ethylene-vinyl alcohol copolymers.

5. The preparation method according to claim 1, characterized in that The matrix resin is a propylene-based polymer, wherein the mass fraction of propylene is greater than 50%; preferably, the melt index of the propylene polymer at 230°C and a load of 2.16 kg is 0.5 to 20 g / 10 min; preferably, the propylene-based polymer includes a propylene homopolymer, a copolymer of propylene and ethylene or an α-olefin.

6. The preparation method according to claim 1, characterized in that The base resin is a butene-based polymer, selected from at least one of butene-1 homopolymer, copolymer of butene-1 and ethylene or C3-C20 α-olefin, isobutylene copolymer, and butadiene homopolymer.

7. The preparation method according to claim 1, characterized in that The matrix resin is polyvinyl butyral, the acetal value of which is 78% to 85% and the hydroxyl value of which is 18% to 20%.

8. The preparation method according to claim 1, characterized in that The molding equipment is a tape casting molding equipment or a calendering molding equipment. Preferably, the molding temperature is 80-200°C.

9. The preparation method according to claim 1, characterized in that In step S2, the second cross-linking agent is added by a coating method, a spraying method, a dipping method or a laminating method.

10. The preparation method according to claim 1, characterized in that The second crosslinking agent is selected from at least one of an organic peroxide crosslinking agent, a non-peroxide crosslinking agent and an inorganic peroxide crosslinking agent, preferably an organic peroxide crosslinking agent; preferably, the one-minute half-life temperature of the second crosslinking agent is lower than 190°C; further preferably, its one-minute half-life temperature is lower than 180°C; further preferably, its one-minute half-life temperature is lower than 170°C; further preferably, its one-minute half-life temperature is lower than 160°C; further preferably, its one-minute half-life temperature is lower than 150°C; most preferably, its one-minute half-life temperature is lower than 140°C; Preferably, the organic peroxide crosslinking agent is selected from di-tert-butyl peroxide, di-tert-amyl peroxide, tert-butyl isopropyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-bis-(tert-butylperoxy)hexane, di-(tert-butylperoxyisopropyl)benzene, tert-butyl peroxide-2-ethylhexyl carbonate, tert-amyl peroxide-2-ethylhexyl carbonate, tert-hexyl peroxide-2-ethylhexyl carbonate, tert-butyl peroxide isopropyl carbonate, tert-butyl peroxide isobutyl carbonate, tert-amyl peroxide isopropyl carbonate Ester, tert-amyl peroxyisobutyl carbonate, tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxyisobutyrate, tert-amyl peroxyisobutyrate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-amyl peroxy-3,5,5-trimethylhexanoate, 2,5-dimethyl-2,5-bis(benzoylperoxy)-hexane, 2,5-dimethyl-2,5-bis-(2-ethylhexanoylperoxy)-hexane, 1,1,3,3-tetramethyl peroxy-2-ethylhexanoate Butyl peroxide, tert-butyl peroxypivalate, tert-amyl peroxypivalate, tert-butyl peroxyneoheptanoate, tert-butyl peroxide neodecanoate, tert-amyl peroxyneodecanoate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-isopropylphenyl peroxyneoheptanoate, α-isopropylphenyl peroxyneodecanoate, 1,1-dimethyl-3-hydroxybutyl peroxyneodecanoate, dibenzoyl peroxide, dilauroyl peroxide, didecanoyl peroxide, succinyl peroxide, 3,5,5-trimethylhexanoyl peroxide, 1, Any one or more of 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-amylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 1,1-bis(tert-amylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, tert-butyl peroxybenzoate, tert-amyl peroxybenzoate, tert-butyl peroxyacetate, and tert-amyl peroxyacetate; Preferably, the added mass of the second cross-linking agent is 0.001-5% of the mass of the base material.

11. The preparation method according to claim 1, characterized in that It also includes step (S3) pre-crosslinking treatment. Preferably, the pre-crosslinking treatment is selected from at least one of thermal crosslinking, radiation crosslinking, UV crosslinking, microwave crosslinking or laser crosslinking; preferably, the pre-crosslinking degree of the film material is 0-70%, preferably 5-30%.

12. The preparation method according to claim 1, characterized in that At least one side surface of the film material has regular or irregular patterns.

13. A thin film material, wherein the thin film material is a single layer or a multilayer, characterized in that: At least one layer of the thin film material is prepared by the preparation method according to any one of claims 1 to 8.

14. Use of the thin film material according to claim 13, characterized in that: The film material is used for packaging of automobile glass, architectural glass, electronic devices or photovoltaic modules.

Citation Information

Patent Citations

  • A composite crosslinking agent for POE encapsulation film and its application

    CN106281122B

  • A weather-resistant biodegradable thin film material, its preparation method and application

    CN114573960B